Analysis of Product Service System Implementation at Scentsual Inspire Perfume Store - Ridha Amira; Nanang Alamsyah; Wendy Febrianty Mardhiyah (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study aims to analyze and evaluate the production process at Scentsual Inspire Perfume by implementing the Product-Service System (PSS) concept using the TUDelft PSS Landscape framework. Through surveys involving store owners, employees, and customers, this research assesses the integration of products and services offered, including perfume personalization, customer education, and an environmentally friendly refill system. The results indicate that the PSS approach supports sustainability, enhances customer satisfaction, and strengthens brand loyalty. However, challenges remain in operational efficiency and the need for supporting technology. These findings provide strategic insights for optimizing a PSS-based business model focused on customer experience and sustainability.